Effects of salinomycin and sodium fumarate on rumen fermentation using rumen simulation technique - KUMAR, M BHARATH; SRIRAM, P; VIJAYARANI, K; VIJAYAKUMAR, C; MATHURAM, L N (The Indian Journal of Animal Sciences, 2010)
The objective of this study was to determine the effect of salinomycin and sodium fumarate on rumen fermentation. The apparent digestibility of basal ration was reduced by salinomycin appreciably at low doses, whereas, sodium fumarate tended to increase it without any change in pH, bacterial count and ammonia nitrogen level. Salinomycin produced a dose-dependent decrease in protozoal count whereas sodium fumarate did not produce any significant change. Microbial protein increased with the addition of salinomycin, whereas sodium fumarate did not produce any significant change in microbial protein synthesis. Salinomycin increased the molar proportion of propionate and reduced the acetate, butyrate and acetate: propionate ratio. Sodium fumarate also reduced acetate: propionate ratio, but increased both acetate and propionate concentrations. Salinomycin and sodium fumarate reduced methane production, however the reduction brought about by sodium fumarate was not comparable with ionophore. Thus, it was concluded that salinomycin and sodium fumarate may be a useful dietary additive for ruminants.